2009
DOI: 10.1634/theoncologist.2009-0070
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenectomy for Gastric Adenocarcinoma: Should West Meet East?

Abstract: After completing this course, the reader will be able to:1. Calculate the lymph node drainage patterns of gastric adenocarcinoma based on the location of the tumor.2. Differentiate and explain the extent of lymphadenectomies performed in different countries.3. Analyze the risks and benefits of performing more extensive lymphadenectomies for gastric adenocarcinoma.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTThe extent of lymphadenectomy that should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…Importantly, a recent study by Lee et al showed that for experts of OG, in cases in which surgical time extension could be accepted willingly, the radicality in lymphadenectomy could be also achieved even during the learning period of LG [105]. Specially, D2 lymphadenectomy is generally recommended as the standard procedure to treat AGCs in East Asia [106]. Successful D2 lymphadenectomy is thus an essential part of radical resection for AGC [107].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a recent study by Lee et al showed that for experts of OG, in cases in which surgical time extension could be accepted willingly, the radicality in lymphadenectomy could be also achieved even during the learning period of LG [105]. Specially, D2 lymphadenectomy is generally recommended as the standard procedure to treat AGCs in East Asia [106]. Successful D2 lymphadenectomy is thus an essential part of radical resection for AGC [107].…”
Section: Discussionmentioning
confidence: 99%
“…In areas without screening programs, such as North America, patients often present late and have a high frequency of nodal involvement 36 . Nodal dissection in gc varies internationally, with surgeons in countries such as Japan and Korea routinely performing the most extensive lymphadenectomies (D2 or greater); most surgeons in North America and many other Western countries perform more limited lymphadenectomies (D1 or less) 37 . The Japanese Gastric Cancer Association published detailed guidelines for the pathologic assessment and staging of gc, describing 4 nodal stations (N1-N4) with the D level of lymphadenectomy based on those definitions of lymph-node station level 38,39 .…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Pancreatic fistula rates were high, thus significantly increasing the morbidity of the D2 lymphadenectomy procedure (Yoon et al, 2009). Maruyama et al described a pancreaspreserving D2 lymphadenectomy that resected the spleen and splenic artery along with the station 10 and 11 lymph nodes (Maruyama et al, 1995).…”
Section: Lymphadenectomy and Pancreaticosplenectomymentioning
confidence: 99%